KONSELING MULTIKULTULAR DALAM PENANGANAN KONFLIK MAHASISWA - Irwanto Gani (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam)
Conflict is the result of unresolved social dynamics, this occurs because the purpose of a person or group of people is not in line with the ideas he understands or in other words different opinions. One of the factors that led to differences of opinion was due to differences in cultural backgrounds, both in terms of ethnicity, religion, gender, place of residence, even to economic, social and educational backgrounds. The emergence of various cultures (multicultural) within the scope of the campus is expected to present a resolution to deal with student conflicts, especially in Makassar. Existing cultural differences require counselors to understand various cultures and how to treat them. It is very important to understand multiculture for a counselor in order to provide awareness that counselors and clients have cultural differences. Multicultural counseling as a field of practice that emphasizes the importance of the uniqueness (peculiarity) of individuals, believes that counselors bring personal values that come from their cultural environment into the counseling process. Briefly it can be stated that multicultural counseling is a process of interaction between counselors and clients who have different cultural backgrounds so that understanding of other cultural concepts is needed especially for counselors to be able to provide assistance effectively and efficiently according to the client's cultural perspective. Keywords: Multicultural Counseling, Conflict